Long period fiber gratings for the mitigation of parasitic laser effects in mid-infrared fiber amplifiers - Heck, Maximilian; Gauthier, Jean-Christophe; Tuennermann, Andreas; Vallee, Real; Nolte, Stefan; Bernier, Martin (Optics Express, 2019)
A concept to mitigate parasitic lasing in mid-IR fiber amplifiers using a single long period fiber grating is shown. Using tightly confined ultrashort laser pulses at 800 nm, a grating was directly inscribed into the core of an erbium doped fluoride glass fiber showing a strong attenuation down to −27 dB at desired wavelength. The concept reveals great potential to improve the average output power and attainable spectral range of low repetition rate in-amplifier supercontinuum generation.
CRIS-Team Scopus Importer:2023-04-20